FROM OBSERVED VISIBLE HUMAN BEHAVIOR TO ANIMATED HUMANOID 3D COMPUTER MODELS - BIVARIATE NOTATIONS AS A PSYCHOLOGICAL METHOD FOR SYSTEMATIC OBSERVATION - Wolfgang Zysk (European Scientific Journal, ESJ, 2014)
Systematic observation of visible phenomena is especially in the exact sciences, e.g. Physics or Chemistry, without doubt one of the most important sources of knowledge and regarded as a prerequisite in those disciplines. For the comparatively young discipline of Psychology, which itself has been counted to the exact sciences since 1982 (ISCU, 1982) precisely detailed, high-resolution and unbiased observation of visible human behavior still remains a challenge. Mere recordings -whether photographic, on film or video- provide no directly measurable or calculable data about complex temporal or spatial human movement sequences, which is absolutely vital for scientific analysis. Finding a method by which visible human behavior can be notated in such a way so as to provide a most accurate true reflection of the observed behavior in the notation itself, has therefore, especially in Psychology, been a problem of the first order for decades. The method of bivariate notation of temporal and spatial visible human movement behavior appears to have proven itself useful, particularly in the context of current work done in solving these problems. With the aid of a comparison between five trend-setting research efforts, this contribution thus aims to provide an overview of how this method has gained efficiency over time, from its early beginnings up to the most current stage of development.